Management of Internationalisation and German-Ukrainian Academic Cooperation (MoI Ukraine) 2019-2024 - (:unkn) unknown (My University, 2024)
The German Academic Exchange Service (DAAD) supports the MoI Ukraine project within the programme “Support for the internationalisation of Ukrainian higher education institutions — Continuing education programmes for administrators at Ukrainian higher education institutions in education and academic management” with funds provided by the Federal Ministry of Education and Research (BMBF). The aim of this DAAD programme line is to provide initial or continued training to employees of Ukrainian higher education institutions in the areas of education and university management and internationalisation through participation in correspondingcourses at German higher education institutions.